The 8-Bit Bureaucrat: Can Video Games Teach Us About Administrative Ethics?. (2nd September 2020) - Exmeyer, Patrick C.; Boden, Daniel
Abstract : Politicians and public administrators have long played both prominent and supporting roles in works of fiction. The field of public administration has a tradition of using fictionalized depictions of administrative processes to understand better the relationship between theory and practice. Portrayals of public servants and government action in video games remain an understudied area, leaving gaps in our understanding related to digital media and bureaucratic characterization. Using Squire's framework of understanding video games as a designed experience, this study examines the elements of administrative ethics and ethical decision making within the video game Papers, Please. Future research will most certainly be required to connect characterization of public service in digital media to public perception and pedagogy of administrative functions. This research aims to catalyze exploration into this concept through illustrated applicability and salience.